Fluctuación poblacional de Gyropsylla spegazziniana (Lizer y Trelles) en plantaciones de Ilex paraguariensis bajo monocultivo tradicional y en sistemas arborizados = Population fluctuation of Gyropsylla spegazziniana (Lizer and Trelles) in Ilex paraguariensis plantations under traditional monoculture and in agroforestry systems - Barth, Sara Regina (2023)
Yerba mate (Ilex paraguariensis St. Hil) is a native species now cultivated on a large scale outside its natural habitat, disrupting the balance of insects, including Gyropsylla spegazziniana, which damages the plants. This study compares Gyropsylla spegazziniana populations in three yerba mate management systems: monoculture, with Toona ciliata, and in native Atlantic Forest. Counts were done over three periods. Yerba mate grown under shade with trees had fewer pests, as shown by trap data. This suggests that cultivating yerba mate alongside trees can help reduce the presence of Gyropsylla spegazziniana and potentially protect the crop.